2005
DOI: 10.1509/jmkg.69.2.114.60762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Expiration Dates and Perceived Risk on Purchasing Behavior in Grocery Store Perishable Categories

Abstract: In this article, the authors examine consumers’ behavior with respect to expiration dates for grocery store perishable products. A better understanding of such behavior can both guide efforts to educate consumers about the risks associated with perishables that are approaching their expiration dates and help managers implement effective promotional strategies for these products throughout the course of their shelf lives. Both of these approaches can help reduce waste due to spoilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
229
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(242 citation statements)
references
References 30 publications
7
229
4
2
Order By: Relevance
“…This happens especially quickly when the quality of the product is affected by the process. Interestingly, WTP is higher in situations in which consumers plan to stop the aging process (for example, by cooking the product right away or freezing it) [26]. When consumers perceive dates on foods as an indicator of freshness and much less as a healthiness or safety indicator, consumers are willing to pay more for the food [27].…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…This happens especially quickly when the quality of the product is affected by the process. Interestingly, WTP is higher in situations in which consumers plan to stop the aging process (for example, by cooking the product right away or freezing it) [26]. When consumers perceive dates on foods as an indicator of freshness and much less as a healthiness or safety indicator, consumers are willing to pay more for the food [27].…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…Quality has been considered to be a key factor influencing consumers' purchasing decisions. Empirical studies have found that consumers are sensitive to the freshness of perishable food and usually give a lower valuation to expiring food [28]. Therefore, previous studies dealing with the deterioration of product quality over time have usually assumed quality dependent demand [29,30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Note that n = 0 represents the case when the quality decays linearly at a constant rate. A survey by Tsiros and Heilman [28] revealed that consumers' willingness to pay decreases linearly through the shelf life for food with relative lower Product Quality Risk (PQR) (such as fresh fruits and vegetables) and exponentially for food with relatively higher PQR (such as pork and chicken). Pawsey [39] proposed a linear model to estimate the quality degradation of fresh vegetables.…”
Section: Model Of Food Degradationmentioning
confidence: 99%
“…Recent studies by Tsiros and Heilman (2005) show that consumers who shop more frequently the category, check use-by dates more often than less frequent shoppers. These researchers also found a willingness of these customers to stop the aging process like cooking or freezing the perishable groceries.…”
Section: Literature Reviewmentioning
confidence: 99%